Salafiah pesantren ideology and KPU Muara Enim's efforts to increase voter participation - Ahmad Naufal Fachriyadi; Afryansyah Afryansyah (Journal of Governance and Accountability Studies, 2023)
Purpose: This research aimed at finding out the ideology of Pondok Pesantren (Ponpes) Dhiya'us Salaf and the people of Karang Agung Village, Lubai Ulu Sub-district, Muara Enim Regency, South Sumatra Province which refused to participate in the General Election (Pemilu) and describe the efforts made by the General Electoral Commission (KPU) of Muara Enim Regency in overcoming this phenomenon. Research methodology: This research was conducted using a qualitative method in the form of a case study approach. Data collection techniques included observations, interviews, and Forum Group Discussion techniques. Results: The results showed that the administrators and the community around Pondok Pesantren Dhiya'us Salaf did not participate in the election for the following reasons: (1) avoiding division, (2) the absence of sanctions, (3) election of Western ideology, and (4) to focus more on their fields. On the other hand, the general electoral commission (KPU) of Muara Enim and South Sumatra made efforts to increase voter participation by (1) providing election socialization and voice education, (2) registering them into the Permanent Voter List (DPT), and (3) breaking up polling stations (TPS). Limitations: Researchers limited aspects of the problem only focused on the efforts of Muara Enim’s KPU and the ideology of Pondok Pesantren Dhiya'us Salaf to create efficient and detailed research. Contribution: In addition to being a solution for breaking the abstainers (Golput) chain, the benefits of this research for the General Electoral Commission (KPU) of Muara Enim and the ranks of the Election Supervisor are a reference material for formulating the right pattern of socialization and political education.